+0  
 
0
29
1
avatar+1380 

Help.

 
NotSoSmart  Jan 14, 2018
Sort: 

1+0 Answers

 #1
avatar+80978 
0

(-3i) (-4i)  =

 

-3 * - 4  * i * i   =

 

12  * i^2           ⇒ [ i^2  = -1  ]

 

12 * -1  =

 

-12

 

 

x + y  =  5   ⇒   y  =  5  - x     (1)

x^2  + y^2  =  25     (2)

 

Sub  (1)  into (2)

 

x^2  +  ( 5 - x) ^2   =  25

x^2  + x^2  - 10x  +  25  = 25   subtract 25 from both sides

2x^2  - 10x  = 0    factor

2x ( x  - 5)      set both facoters to 0 and solve for x and x  =  0   or  x  = 5

 

 

Using (1)

 

When x  = 0,     y  =  5 - 0   =  5

and

When  x  = 5,  y  = 5 - 5  =   0

 

So the solutions are    (0, 5)  and  (5, 0 )

 

 

cool cool cool

 
CPhill  Jan 14, 2018

21 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details